Screening and isolation of the potential soil bacteria for ability to produce antibiotics / Rashidah Abd Halim - Abd Halim, Rashidah (2017)
Antibiotics are a group of medicines which produced by microbes and used to treat any infections. Bacteria are the most producers for antibiotic. Bacteria producing antibiotic normally had been found in soil. Soil is one of potential habitat to isolate bacteria producing antibiotic. Thus, the aims of this study were to screen and to isolate the potential bacteria producing antibiotic from soil sample. Soil suspension was prepared from soil sample of Hutan Simpan UiTM Negeri Sembilan by diluting one gram of soil into nine ml of water prior incubation at 37°C for 24 hours. After incubation period, two potential bacteria were successfully identified namely bacteria A and bacteria B. Morphological characteristics was carried out to characterize both potential bacteria. Result demonstrated that both bacteria have similar bacilli structure with chain arrangement. However, gram staining characterized bacteria A as Gram positive and bacteria B as Gram negative. Antibacterial activity was performed to identify the potential of both bacteria producing antibiotic against three bacteria namely Staphylococcus aureus, Escherichia coli and Shigella species. Result showed a positive result in bacteria A by performing a clear zone against bacteria Staphylococcus aureus with average diameter of 5 mm. Bacteria B showed a negative result for all bacteria tested. Biochemical test performed in bacteria A indicated that it demonstrate the similar characteristic with Bacillus species.